Strategi Pemberdayaan Guru Dan Orang Tua Anak Usia Dini Di Kecamatan Mapanget Kota Manado - Tampi, Fera Luicia (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to analyze strategies for empowering teachers and parents in the implementation of early childhood education (ECE) in Mapanget District, Manado City. Empowerment is understood as an effort to enhance the capacity, participation, and collaboration between teachers and parents to support children’s holistic development. The research employed a qualitative descriptive approach, with data collected through interviews, observations, and document studies involving five ECE institutions and fifteen informants consisting of principals, teachers, and parents. The results show that teacher empowerment is carried out through continuous training, academic supervision, and reflective learning forums. Parent empowerment is implemented through parenting programs, active involvement in school activities, and two-way communication between teachers and families. The main supporting factors include local government policy support and a collaborative community spirit, while the main challenges are parents’ low educational literacy and limited institutional resources. This study recommends strengthening community-based school–family partnerships and developing participatory empowerment models suited to the local context.